Disability Among Ebola Survivors and Their Close Contacts in Sierra Leone: A Retrospective Case-Controlled Cohort Study. (20th August 2017) - Jagadesh, Soushieta; Sevalie, Stephen; Fatoma, Richard; Sesay, Foday; Sahr, Foday; Faragher, Brian; Semple, Malcolm G; Fletcher, Tom E; Weigel, Ralf; Scott, Janet T
Abstract: Ebola survivors (21/27 [77.8%]) suffered more disability than their close contacts (6/54 [11.1%]) (adjusted odds ratio, 23.5 [95% confidence interval, 6.5–85.7]; P < .001) when measured by the Washington Group Disability Extended Questionnaire. Major limitations in vision, mobility, cognition, and affect were observed in survivors 1 year following the 2014–2016 Ebola outbreak, highlighting the need for long-term rehabilitation.